Extraction of soursop oil (Annona muricata L.) by ultrasonic technique: Chromatographic evaluation and thermal characterization - Fonseca, Mariana [UNESP]; Ferreira, Leonardo M. B. [UNESP]; Soares, Rosana A. M.; Kobelnik, Marcelo; Fontanari, Gustavo G.; Crespi, Marisa S. [UNESP]; Ribeiro, Clóvis A. [UNESP] (Springer Nature, 2018)
The soursop, Annona muricata L., Annonaceae family is a fruit mostly found in the northern and northeastern of Brazil, the Caribbean, and Central America. Extraction of the soursop seed oil was carried out in an ultrasound bath, yelling a 20% w/w yield, and fatty acids profile analyzed by gas chromatography indicated a predominance of stearic, oleic, and palmitic acid, in a relative percentage of 40.47%, 31.87%, and 19.82%, respectively. Thermogravimetry (TG), derivative thermogravimetry (DTG), and differential scanning calorimetry (DSC) were used to characterize the thermal behavior of this oil. The phase transition of this oil was evaluated by DSC analysis, on heating and cooling modes. Additionally, the thermal behavior analysis evaluated by TG and DTG was carried out with two different sample masses and three heating rates (5, 10, and 20 °C min−1) under oxidant and inert purge gases. The cooling and heating DSC curves indicate the influence of saturated and unsaturated fatty acids in the thermal behavior. The activation energy (Ea) was obtained with the isoconversional methods proposed by Capela and Ribeiro, Ozawa and Friedman, and the resultant data lead to a dependence on the sample mass and purge gases, which show several kinetic patterns.
Keywords: Chromatography; Kinetic evaluation; Soursop oil; Thermal behavior; Ultrasonic bath